2013 IEEE International Conference on Body Sensor Networks 2013
DOI: 10.1109/bsn.2013.6575468
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic porosity generation in outer hydrogel membranes to offset sensitivity loss in implantable glucose sensors

Abstract: The function of implantable glucose sensor is hindered by post-implantation effects such as biofouling and negative tissue responses both of which lead to permeability reducing fibrous encapsulation. Utilization of drug-eluting composite coatings based on dexamethasone-containing poly (lactic-coglycolic) acid (PLGA) microspheres and poly (vinyl alcohol) (PVA) hydrogel matrix has been shown to suppress inflammation over a period of 1-3 months. Herein, it is shown that these coatings provide another auxiliary ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As previously reported, Dex-loaded porous coatings had a porosity of ~ 85% and a pore size of ~76 μm [25], features which have been shown to enhance tissue vascularization and disrupt collagen capsule formation around implanted sensor leads [11, 22]. Moreover, several studies have reported on the angiogenic effects of texturing to increase vascularity around medical implants [11, 25, 3335]. Though the exact mechanism by which topographical cues promote angiogenesis and tissue integration have yet to be elucidated, it is believed that pores within the 20–100 μm provide an optimal environment for transport of cellular by-products and migration of endothelial cells [39].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As previously reported, Dex-loaded porous coatings had a porosity of ~ 85% and a pore size of ~76 μm [25], features which have been shown to enhance tissue vascularization and disrupt collagen capsule formation around implanted sensor leads [11, 22]. Moreover, several studies have reported on the angiogenic effects of texturing to increase vascularity around medical implants [11, 25, 3335]. Though the exact mechanism by which topographical cues promote angiogenesis and tissue integration have yet to be elucidated, it is believed that pores within the 20–100 μm provide an optimal environment for transport of cellular by-products and migration of endothelial cells [39].…”
Section: Discussionmentioning
confidence: 90%
“…Dex is a potent glucocorticoid associated with diminished activation of immune cells and up-regulation of anti-inflammatory cytokines [21, 29, 30], yet localized delivery of Dex is often accompanied by decreased vascularity at the sensor-tissue interface [20, 21, 3032]. It is also well established that surface texturing with feature sizes on the order of cellular dimensions can induce blood vessel formation around medical implants [11, 25, 3335]. …”
Section: Discussionmentioning
confidence: 99%